Use of reduced concentrations of tetrazolium solutions for the evaluation of the viability of peanut seed lots - Bittencourt, S. R.M. [UNESP]; Vieira, R. D. [UNESP] (My University, 1997)
The possibility of reducing the concentration of the working solution used in the tetrazolium test for peanut seeds (Arachis hypogaea L.) with or without seedcoats was studied. Tetrazolium solutions of different concentrations (0.05%, 0.075% and 0.1%) were tested at the temperatures of 35 and 40°C, for determining the time needed for the seeds to reach proper staining. The efficiency of the selected treatments in evaluating the viability potential of the seeds was determined by comparing the results of the tetrazolium tests with those obtained by standard germination (using sand and rolled paper towel as substrata) and seedling emergence in the field tests. Staining the seeds without seedcoat in 0.05% tetrazolium solution for three hours at 40°C yielded efficient results. On the other hand, reduced concentrations can be employed in the staining process of seeds with seadcoat; however, this method requires a higher consumption of tetrazolium salt, longer staining time as well as a higher ability and availability of time for embryo evaluation, since the cross-cutting of seeds is much more difficult in the presence of the seedcoat and the occurrence of damage to the outer surface of the cotyledons cannot be determined.